A Mini-Open Approach to Medial Pinning in Pediatric Supracondylar Humeral Fractures May Be Safer Than Previously Thought. (5th January 2022) - Rees, Andrew B.; Schultz, Jacob D.; Wollenman, Lucas C.; Moore-Lotridge, Stephanie N.; Martus, Jeffrey E.; Schoenecker, Jonathan G.; Mencio, Gregory A.
Abstract : Background: Displaced pediatric supracondylar humeral fractures (SCHFs) are stabilized after reduction by smooth pins. Although some SCHFs are biomechanically stable after lateral-only entry pinning (lateral pinning), an additional medial entry pin (cross-pinning) confers superior stabilization in some SCHFs. There is a recognized risk of iatrogenic ulnar nerve injury with medial entry pinning. The best existing evidence has estimated an iatrogenic ulnar nerve injury rate of approximately 3.4% in cross-pinning. In similar studies, the rate of iatrogenic nerve injury (all nerves) in lateral pinning is estimated at 1.9%. This study aimed to use a large, single-center, single-technique (mini-open) retrospective case series to determine the rate of iatrogenic ulnar nerve injury in cross-pinning. Methods: Patients undergoing percutaneous cross-pinning via the mini-open technique for SCHFs from 2007 to 2017 were retrospectively reviewed. Injury characteristics, operative variables, fixation technique, and complications, such as iatrogenic nerve injury, were recorded. Patients who underwent operative treatment at another hospital, had no postoperative follow-up, or died due to polytrauma were excluded. Results: In this study, 698 patients undergoing cross-pinning during the study period were identified. Patients treated with cross-pinning had severe fractures, including a total of 198 preoperative neurovascular injuries (28.4%), 32 patients (4.6%) with skin tenting, and 19 patients (2.7%) with open fractures. Iatrogenic nerve injury was reported in 3 cases (0.43%), all of which affected the ulnar nerve. In 2 of 3 cases of iatrogenic nerve injury, the ulnar nerve symptoms resolved at a mean follow-up of 15 weeks. Conclusions: The mini-open approach for medial pin insertion is safer than previous estimates. Here, in the largest single-center study of cross-pinning for SCHFs, the iatrogenic ulnar nerve injury rate of 0.43% was nearly 10 times lower than estimated rates from recent meta-analyses. Considering all nerves, the iatrogenic injury rate for this cross-pinning cohort was also lower than the estimated iatrogenic nerve injury rate for lateral pinning. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.